English Teaching Reform from the Perspective of Students - Tian, Qinxia (Journal of Education and Educational Technologies, 2023)
English is an important course in college and a crucial tool for students' future development. With the development of society, the previous teaching models are no longer applicable to the current college English classroom. Therefore, we need to reform college English teaching. This article aims to discuss how to do a good job in English reform from the perspective of students. The present study yields several noteworthy conclusions concerning the relationship between students' anxiety and motivation in online English learning, and their influence on English language performance. First and foremost, the analysis unveiled that participants commonly encounter anxiety within the context of online English classes, specifically in terms of dread of negative evaluation and communication apprehension. Nonetheless, a significant portion of the respondents indicated a moderate to strong level of motivation for learning English online. They expressed a moderate to strong degree of motivation, encompassing both instrumental and integrative aspects of language learning. Secondly, a crucial positive correlation was found between online English anxiety and online English motivation. While previous studies have commonly presented a negative association between apprehension and motivation, some researchers suggest that anxiety can serve as a source of energy that motivates students. Nevertheless, it is important to note that elevated levels of anxiety adversely affect academic performance, underscoring the necessity for teachers to attentively monitor the psychological state of students experiencing heightened anxiety. Moreover, learners’ performance in English was substantially associated with both foreign language apprehension and English learning drive. In order to improve outcomes in online English classes, it is imperative for language teachers and learners to address and mitigate elevated levels of anxiety. Implementing effective strategies such as establishing attainable goals, fostering a supportive and relaxed learning environment, encouraging the exchange of language learning experiences and emotions, providing ample opportunities for language practice, and offering regular encouragement and recognition can contribute to anxiety reduction and enhance students' overall drive in acquiring the target language. Additionally, enhancing learners' understanding of the significance of English , cultivating their enthusiasm for the language, bolstering their self-assurance, fostering favorable attitudes towards English, offering commendation and constructive feedback, analyzing factors behind both weak and strong English performance, and promoting activities such as reading books, listening to English music, watching English movies, and engaging with international students can play a vital role in augmenting students' enthusiasm to learn English. With increased motivation, learners may become more driven and proactive in using the language, leading to reduced anxiety in learning English. Finally, further examination of the causes of foreign language anxiety that influence student anxiety is recommended to deepen teachers' and researchers' understanding of students' mental states. Conducting interviews and observations related to foreign language anxiety can provide valuable insights for future research. Additionally, considering the study's focus on a representative higher vocational college EFL setting, the findings and implications have broader applicability to comparable EFL contexts across the country. However, further investigations in diverse settings with students from different backgrounds are needed to gain a comprehensive understanding of the relationship.